A criação poética de Patativa do Assaré - Pinheiro, Maria do Socorro (2006)
The major goal of this research work is to investigate the process of creation of an important poet of the literature of the state of Ceara, Antonio Gonçalves da Silva, known as Patativa do Assaré. The research consisted of a bibliographic study through which a number of his poems were selected and analised. On observing his process of creating verses, memory, voice, language, and subject, we came to the following findings: his poetic work is all marked by orality. His poems were created and kept in his mind as if they were created to be told in a public solemnity. His poems were only put on paper after some time. It is worth stating that this trace of orality is perceived not only when their poems were told in public, but also when they were put in written form. This feature of orality through the writing is responsible for a kind of dynamics, which gives a really meaningful value to the combination and harmony of the verses. It is observed that the writing does not interfere with the origin of the poet’s work. The writing function is to register and disseminate it. The poet’s ability of producing orality is also clearly observed through origin, elaboration, and memorization of his verses. The country is the place where he produces his verses. Therefore, we can realize how the social dimension, beauty, language and the relations between nature and culture are strong in his poetry. This means that the country provides him with a kind of poetry which aims at showing the unfair conditions of living of those who live there. To sum up, his poetry is universal for its quality; and constitutes a strong voice that vibrates representing the country.